Achieving Relative Time Synchronization in Wireless Sensor Networks - Salman Ahmed; Feng Xiao; Tongwen Chen (Journal of Control Science and Engineering)
Time synchronization is required for a variety of distributed control applications in wireless sensor networks (WSNs). In this paper, a novel distributed time synchronization technique for WSNs is presented. The proposed technique does not require all the sensor nodes to have the same time periods or starting times. Furthermore, the communication topology of the WSN is not assumed to be static; it can change with time. The WSN is modeled by a time-varying discrete-time system. The objective is to design local control inputs to achieve relative time synchronization by using the neighbor sensor nodes information. By employing tools from nonnegative matrix and graph theories, the convergence analysis is presented. Numerical examples are presented to demonstrate the effectiveness of the proposed protocol.